The Effect of Blood Pressure Measurement Training on Early Detection and Control Efforts of Hypertension Patients in Health Service Facilities - Veronika Toru; Maria Kareri Hara; Leni Landudjama (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Hypertension or high blood pressure is the result of systolic and diastolic blood pressure that is too high ≥140/90 mmHg. Hypertension is one of the causes of premature death worldwide Reducing the prevalence of hypertension by 33% in 2020-2030 is one of the global targets of non-communicable diseases. Blood pressure (BP) measurements performed by individuals and families have a high potential to improve the diagnosis and management of hypertension. The implementation of blood pressure measurements is carried out through increasing education and training for individuals and families in measuring blood pressure independently. Early detection through self-measurement of blood pressure and control of hypertension by health services is an effort to control hypertension. This study aimed was to identify the effect of blood pressure measurement training on early detection and control efforts for hypertensive patients at health service facilities. This research uses a pre-experimental research design with a one-group pretest-posttest design. The sampling technique used a purposive sampling method. with a total sample 24 respondents. The form of treatment is providing training to measure blood pressure using a digital blood pressure monitor. Before the training was conducted, the respondents' ability to measure BP was measured first through a pre-test (initial observation before the intervention, after which the intervention was given (BP measurement), then a post-test (final observation) was conducted after the treatment was given, using the same measuring instrument. The result of this study, there was an effect of blood pressure measurement training on early detection and control efforts of hypertension patients in health care facilities with a p-value of 0.000. Independent blood pressure measurement training in individuals with hypertension has a positive impact on increasing knowledge and changing individual behavior in conducting early detection and control efforts of hypertension in healthcare facilities.